Implementation of Biogas Systems in Broiler Farms to Improve Biosecurity and Sustainable Economic Value - Sri Wahyuni; Dadang Jaenudin; Rindi Handayani (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the application of an integrated biogas system in closed house broiler farms as an effort to improve energy efficiency, biosecurity, and sustainable economic value. The research was carried out at PT Zara Propertifarm Indonesia, Bogor Regency, with a system engineering approach and cost-benefit analysis. The results of the study show that the application of biogas is able to reduce LPG consumption by 50% and save energy costs of up to IDR 1,500,000 per production cycle. In addition, there was an increase in the average weight of chickens from 1.82 kg to 1.97 kg per head and a decrease in the mortality rate from 4.8% to 3%. The fermented waste was successfully processed into solid and liquid fertilizer with laboratory quality according to the SNI 19-7030-2004 standard. Economic analysis shows that the total benefits reach IDR 4,760,000 per 1,000 chickens per cycle. Socially, this activity increased the capacity of 15 MBKM students and 8 partner farmers through biogas system operational training. These findings confirm that the biogas system can be a model of sustainable teaching farms based on renewable energy that supports the transition to low-emission agriculture and a circular economy in the livestock sector